Bioactivity of Azadirachta Excelsa Jack. Extractives on Selected Insects - T. Lardizabal, Maria Lourdes (1998)
Azadirachta excelsa Jack. is a fast growing timber species that has been newly chosen as a potential forest plantation species to overcome timber deficit for domestic consumption in future. This species like Azadirachta indica is suspected to contain biologically active compounds that is detrimental on insects. Many studies have been done on the A. indica, a relative species to A. excelsa, however, studies on A. excelsa are still in preliminary stages. Therefore, the aim of this study was to evaluate the effect of A.excelsa crude extractives towards three selected insect pests, (i.e. Spodoptera Iitura, Callosobruchus chinensis and Coptotermes curvignathus). A preliminary test to evaluate the susceptibility of A. excelsa wood towards termites, compared to Koompasia malaccensis, Hevea brasiliensis and Pinus caribaea was also conducted. In the first part of the study, the A.excelsa plant extracts were extracted from different plant parts (i.e. leaf, bark, trunk, twigs and branch) using a range of polar to non-polar solvents, namely hexane, petroleum ether, toluene, ethyl acetate and methanol. The plant extractives were sampled and analysed through Thin Layer Chromatography (TLC) and Infrared Spectrocopy (IR). In the second part of the study, bioassay tests were conducted on the selected insects. The insects were exposed to the plant extractives prepared at three concentration levels (i.e. 250 ppm, 500 ppm and 1000 ppm) and the solvents (0 ppm) as the control, by feeding the insects with treated food source. The S. litura larvae were fed with castor leaf discs soaked in the respective extractives. The C. chinensis adults were exposed to mungbean seeds that had been soaked in the plant extrctives while the C. curvignathus were fed with treated filter paper. In the last part of this study, the A. excelsa wood together with the other three wood species mentioned earlier, were exposed to the termites both in the laboratory and field.